Factors that Influence the Incidence of Stunting in Toddlers at Working Area of UPT Belawan Health Center Medan City in 2025 - Putri Rahmarianti; Zuraidah Nasution; Ramadhani Syafitri Nasution (Universitas Ibn Khaldun Bogor, 2026)
Stunting is a condition in which toddlers have a shorter length or height compared to their age. This condition is measured by length or height being below minus two standard deviations of the median according to the WHO Child Growth Standards. This study aims to identify and analyze the factors that influence the incidence of stunting in toddlers at working area of UPT Belawan Health Center, Medan City in 2025. This study used a quantitative design with a cross-sectional approach. The population consisted of all mothers with toddlers aged 24–59 months, totaling 2,560 individuals. A random sampling technique was used to obtain 97 respondents, plus an additional 10% reserve, resulting in 107 participants. Data collection was done through questionnaires, with primary, secondary, and tertiary data sources. Data were analyzed using univariate, bivariate, and multivariate analyses. The statistical tests applied included chi-square and multiple logistic regression. The findings revealed that exclusive breastfeeding duration (p = 0.013), the timing of complementary feeding (p = 0.002), birth weight (p = 0.001), sanitation (p = 0.004), and history of infectious diseases (p = 0.001) significantly influenced the incidence of stunting. The most dominant factor affecting stunting was the history of infectious diseases, with an Exp(B) value of 7.378. The study concluded that exclusive breastfeeding duration, timing of complementary feeding, birth weight, sanitation, and history of infectious diseases were significantly associated with stunting incidence in toddlers. It is suggested that the government, particularly health workers at public health centers, evaluate programs and enhance health promotion regarding stunting to reduce its prevalence in Indonesia.